2018
DOI: 10.18632/oncotarget.24310
|View full text |Cite|
|
Sign up to set email alerts
|

First-in-human phase 1 study of the BTK inhibitor GDC-0853 in relapsed or refractory B-cell NHL and CLL

Abstract: GDC-0853 is a selective, reversible, and non-covalent inhibitor of Bruton’s tyrosine kinase (BTK) that does not require interaction with the Cys481 residue for activity. In this first-in-human phase 1 study we evaluated safety, tolerability, pharmacokinetics, and activity of GDC-0853 in patients with relapsed or refractory non-Hodgkin lymphoma (NHL) or chronic lymphocytic leukemia (CLL). Twenty-four patients, enrolled into 3 cohorts, including 6 patients who were positive for the C481S mutation, received GDC-0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 39 publications
0
63
0
1
Order By: Relevance
“…Fenebrutinib (GDC-0853, RG7845) is an orally administered BTK inhibitor that is highly selective and noncovalent, leading to reversible binding, intended to block B cell proliferation and the resulting excessive immune response seen in autoimmune disorders (21). Fenebrutinib has previously been evaluated in healthy subjects (22) and patients with resistant B cell lymphoma or chronic lymphocytic leukemia (23).…”
Section: Bruton's Tyrosine Kinase (Btk) and Fenebrutinibmentioning
confidence: 99%
“…Fenebrutinib (GDC-0853, RG7845) is an orally administered BTK inhibitor that is highly selective and noncovalent, leading to reversible binding, intended to block B cell proliferation and the resulting excessive immune response seen in autoimmune disorders (21). Fenebrutinib has previously been evaluated in healthy subjects (22) and patients with resistant B cell lymphoma or chronic lymphocytic leukemia (23).…”
Section: Bruton's Tyrosine Kinase (Btk) and Fenebrutinibmentioning
confidence: 99%
“…Fenebrutinib appears unique due to its high selectivity (for BTK versus nontarget kinases) relative to other BTK inhibitors as well as its noncovalent binding mode (15). Phase I clinical studies have shown fenebrutinib to be well-tolerated with no safety signals precluding further clinical development (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…GDC-0853 suppresses downstream BCR signaling, resulting in downregulation of the NF-κB pathway and inhibition of cell proliferation [112,113]. In a phase I study, GDC-0853 was indicated in 24 patients with relapsed or refractory non-Hodgkin lymphoma (10 patients) or CLL (14 patients) [114]. Six patients were positive for C481S mutation.…”
Section: Gdc-0853mentioning
confidence: 99%